The Potential Impact of Entrepreneurial Skills on University Pre-Service Chemistry Education Teachers’ Achievement - Ojobola, Folasade; Esan, Oyemomi; Bada, Abiodun; Babalola, Femi (COMPETITIVE: Journal of Education, 2025)
We examined the effect of entrepreneurial skills on the academic achievements of university pre-service chemistry teachers in the field of chemical production. Quasi-experimental research design, which involved 80 pre-service chemistry teachers, was adopted for the study. Four research questions and three null hypothesis were answered and tested for acceptance or otherwise respectively. Entrepreneurship Chemistry Achievement Test (ECAT) was employed as the primary assessment tool. The test items were formulated based on the concepts within chemical production, a sub-topic under polymer chemistry. The three research questions were answered using mean and standard deviation while the hypothesis were tested using t-test. Findings revealed that pre-service teachers who participated in hands-on exercises related to chemical production exhibited superior achievement compared to those who did not engage in practical activities. Based on this finding, it was recommended that equipping chemistry education pre-service teachers with technical skills, wider and deeper knowledge of chemical analysis tools in addition to professional skills should be integrated not only into the school curriculum, and for improved academic achievement, but for wealth creation, poverty reduction and youths’ self–employment.